Effects of organic and inorganic copper on cecal microbiota and short-chain fatty acids in growing rabbits - Du, Yanan; Tu, Yun; Zhou, Zeyang; Hong, Rui; Yan, Jiayou; Zhang, Gong-Wei (Frontiers in Veterinary Science, 2023)
Copper (Cu) is an essential trace element for the growth of rabbits. This study aimed to investigate the effects of different Cu sources on intestinal microorganisms and short-chain fatty acids (SCFAs) in growing rabbits. A total of 120 New Zealand rabbits, aged 35 days, were fed diets containing two inorganic (cupric sulfate and dicopper chloride trihydroxide) and two organic [cupric citrate (CuCit) and copper glycinate] Cu compounds. Each dietary source contained 20 mg/kg of Cu. Cecum microbiota and SCFAs were investigated via 16S rDNA gene amplicon sequencing and gas chromatography, respectively. For alpha diversity assessment analysis, the organic Cu groups were less variable than the inorganic Cu groups. Compared with the inorganic Cu groups, the CuCit group had a significantly higher relative abundance of Rikenella and Paeniclostridium genera, while the CuCit group had a significantly lower relative abundance of Novosphingobium and Ruminococcus genera (P < 0.05). The t-test analysis revealed that the CuCit group had a significantly higher relative abundance of Paeniclostridium, Tissierella, Lachnospiraceae_NK3A20_group, Enterococcus, and Turicibacter genera compared with the inorganic Cu groups. Among the SCFAs, the butyric acid level significantly decreased in the organic Cu groups than in the inorganic Cu groups. The relative abundance of Rikenella and Turicibacter genera was significantly negatively correlated with the butyric acid level in the CuCit group compared with both inorganic Cu groups. These results revealed that the organic Cu (CuCit) group had an increased abundance of Rikenella, Enterococcus, Lachnospiraceae_NK3A20_group, and Turicibacter genera in the rabbit cecum.